(untitled) (Intent Research Scientific Journal, 2025)
Wine poetry flourished during the Mamluk era, much like in earlier periods. Poets, including Al-Mushid, paid attention to its type, taste, aroma, color, and vessels, imbuing it with their consciousness, creativity, and genius. Wine, for Al-Mushid in particular and for Mamluk-era poets in general, was a source of poets’ ecstasy and a stimulus for their emotions; consequently, their poetic texts are filled with references to it, rich in depictions of its qualities and the comfort and tranquility it brings to the soul. It is considered the temperament of the mind and a solace for the melancholic. They approached it eagerly and passionately, described its effects and those of its drinkers, and encouraged drinking it morning and evening, emphasizing the greatness and beauty of the act, and the loss of happiness for those who abstain.